2005
DOI: 10.1002/jez.a.128
|View full text |Cite
|
Sign up to set email alerts
|

Time-related interdependence between low-frequency cortical electrical activity and respiratory activity in lizard,Gallotia galloti

Abstract: Electroencephalograms of medial cortex and electromyograms of intercostal muscles (EMG-icm) were simultaneously recorded in the lizard, Gallotia galloti, during two daily time periods (at daytime, DTP: 1200-1600 h; by night, NTP: 0000-0400 h), to investigate whether a relationship exists between the respiratory and cortical electrical activity of reptiles, and, if so, how this relationship changes during the night rest period. Testing was carried out by studying interdependence between cortical electrical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…5b ). Since respiration has been linked to cortical activity in both mammals 59 and lizards 60 , we used video recordings to track the movements of the ribcage area, which is a proxy for respiration dynamics during sleep (Fig. S3 , Video S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…5b ). Since respiration has been linked to cortical activity in both mammals 59 and lizards 60 , we used video recordings to track the movements of the ribcage area, which is a proxy for respiration dynamics during sleep (Fig. S3 , Video S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some reptiles seem to have a 'reversed' electroencephalogram, in which the awake period is characterized by waves of slow frequency and large amplitude, sometimes interrupted briefly by periods of desynchronized activity. Furthermore, the amplitude of the signals diminishes with the level of activity of the animal (21,22), and it has been suggested that turtles have a single sleep period that mixes the properties of REM and NREM periods of mammals (23); a similar proposition has been made for sleep in Echidna (14).…”
Section: Introductionmentioning
confidence: 93%
“…This occurs, for example, in regional hysteresis losses when a voluntarily shifted, regional change -which might compose the electroencephalographic pattern -increases or decreases the causal modifications ("inflections") of this field's dynamic, while proceeding conversely (respectively, decreasing or increasing them) for its occasional "neglected" background. What matters is the course of the coupled inflections, not the electroencephalographic synchronization or desynchronization itself: as commented, reptiles and mammals keep paying attention on opposite electroencephalographic regimes; moreover, electroencephalographic activity includes a great deal of potential variations concomitant but unrelated to the mind's actions and reactions; see, e. g., De Vera et al (2005). Thus, whether stirred by the circumstanced psyche (voluntary attentional shift) or by her brain's physiology (involuntary attentional shift), the brain's resulting regular action upon its circumstanced psyche enacts, in her, intonated reactions with variable noergy, that is, more or less interpretable in operational terms.…”
Section: How Do Perceived Features Fade Due To Inattention?mentioning
confidence: 99%